Just neighbors? : research on African American and Latino relations in the United States - Telles, Edward Eric, 1956-; Sawyer, Mark Q., 1972-; Rivera-Salgado, Gaspar (Russell Sage Foundation, 2011)
Blacks and Latinos have transformed the American city- together these groups now constitute the majority in seven of the ten largest cities. Large-scale immigration from Latin America has been changing U.S. racial dynamics for decades, and Latino migration to new destinations is changing the face of the American south. Yet most of what social science has helped us to understand about these groups has been observed primarily in relation to whites- not to each other. This book challenges the traditional black-white paradigm of American race relations by examining African Americans and Latinos as they relate to each other in the labor market, the public sphere, neighborhoods, and schools. The book shows the influence of race, class, and received stereotypes on black-Latino social interactions and offers insight on how finding common ground may benefit both groups. From the labor market and political coalitions to community organizing, street culture, and interpersonal encounters, this book analyzes a spectrum of Latino-African American social relations to understand when and how these groups cooperate and compete. -- from Book Jacket.